2019
DOI: 10.22159/ajpcr.2019.v12i3.31018
|View full text |Cite
|
Sign up to set email alerts
|

Design and in Vitro Characterization of Floating Tablets of Metronidazole

Abstract: Objective: The objective of the present study was to formulate the effervescent floating matrix tablet of metronidazole and to evaluate the effect of varying concentrations of hydrophilic polymers on drug release. Methods: Drug excipients interaction was studied by Fourier transform infrared spectrophotometer. The effervescent floating matrix tablets were prepared by direct compression technique using hydroxypropyl methylcellulose (HPMCK4) and xanthan gum alone and in combination as release retardants. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The same trend exhibited by F4 and F6 prepared with HPMC alone or in combination with sodium alginate had better compressibility followed by retarded floating behavior. These results are in agreement with the findings of other authors who manipulated flow behavior and compaction of different grades of HPMC [ 29 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The same trend exhibited by F4 and F6 prepared with HPMC alone or in combination with sodium alginate had better compressibility followed by retarded floating behavior. These results are in agreement with the findings of other authors who manipulated flow behavior and compaction of different grades of HPMC [ 29 ].…”
Section: Resultssupporting
confidence: 93%
“…It was observed that HPMC K4M, due to less viscosity and low molecular weight, could not maintain matrix integrity sufficiently when used alone and did require sodium alginate combination to control the drug release. It is important to study matrix integrity of the floating tablets, because lack of tablet physical integrity could result into smaller fragments after being broken down and an escape from GIT [ 29 ]. Drug release from floating tablets up to larger extent does not depend on agitational intensity or rotational speed of the release media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the use of HPMC resulted in an immediate release of drugs without any control of drug release. However, it showed quiet control in drug release when used in combination with another polymer, which was also observed in research by Eswaraiah et al that HPMC due to its lower viscosity and low molecular weight, could not maintain matrix integrity sufficiently when used alone and did require combination of other polymer to control drug release [28]. The data of dissolution revealed that the combination use of the polymer showed an increase in total floating time than used in individual form.…”
Section: In-vitro Dissolution Testmentioning
confidence: 65%
“…Chinna eswaraiah et al, (2019) 17 clarifies the effervescent floating matrix tablet of metronidazole and assesses the impact of fluctuating groupings of hydrophilic polymers on sedate discharge. Drug excipients association was concentrated by Fourier change infrared spectrophotometer.…”
Section: Multiple-unit Dosage Formsmentioning
confidence: 99%